Computer Science, asked by abhisheak991, 3 months ago

What is h(41)-h(40), given the definition of h below?


def h(n):
s = 0
for i in range(1,n+1):
if n%i > 0:
s = s+1
return(s)

Answers

Answered by gulshanyadav63
0

answer is 1 because s-s=1

Answered by dreamrob
0

Given:

def h(n):

   s = 0

   for i in range(1,n+1):

       if n%i > 0:

           s = s+1

   return(s)

Answer:

h(41) - h(40) = 7

Therefore, 7 is the answer of h(41) - h(40)

Explanation:

h(41)

function h will be called and 41 will be passed to n

Loop will start from i = 1 and will go till i = 41

i          if(n%i > 0)       s=s+1

1             false               0

2            true                 1

3            true                 2

4            true                 3

5            true                 4

.

.

.

39          true               38

40          true               39

41           false              39

So, h(41) = 39

h(40)

function h will be called and 40 will be passed to n

Loop will start from i = 1 and will go till i = 40

i          if(n%i > 0)       s=s+1

1             false               0

2            false               0

3            true                 1

4            false                1

5            false                1

6            true                 2

7            true                 3

8            false                3

9            true                 4

10           false               4

11            true                 5

.

.

.

19           true               13

20          false              13

21           true               14

.

.

.

39          true              32

40          false            32

So, h(40) = 32

Therefore, h(41) - h(40) = 39 - 32 = 7

Similar questions